Concept of Good Governance in Jurisprudence: The Russian Experience and Practice - Kireeva, Elena (Public Governance, Administration and Finances Law Review, 2018)
In the given contribution the author analyses the Russian experience in the implementation of the concept of good governance. The research highlights the issues in the sphere of public management, which have been only partially resolved in the course of the administrative reform in the Russian Federation. Using the method of comparative legal analysis and monitoring the author reviews the existing approaches to the concept of good governance in the scientific literature and explores the implementation of the principles of good governance enshrined in the EU documents in the Russian law.